Clinical Profile and Outcomes of Geriatric Patients Admitted to Level III Intensive Care Unit of a Tertiary Care Hospital of Nepal: A Retrospective Observational Study - Piya, Buna; Koirala, Sabin; Adhikari, Suraj; Karki, Arjun (Journal of Nepalese Society of Critical Care Medicine, 2026)
Background and aims: Ageing global population results in an increasing burden of critically ill elderly patients requiring intensive care. Data on clinical characteristics and outcomes of geriatric patients in intensive care unit (ICU) of Nepal is limited. This study aimed to evaluate the clinical profile and outcomes of geriatric patients admitted to a level III ICU of a tertiary care hospital in Nepal.Methods: This retrospective observational study was conducted using registry data from the Nepal Intensive Care Research Foundation (NICRF). Patients aged ≥60 years admitted to the ICU of the Hospital of Advanced Medicine and Surgery (HAMS) between April 1, 2024, and March 31, 2025, were included in the study. Patients with incomplete data or ICU stay